2009
DOI: 10.1002/pmic.200800214
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the podocyte proteome in response to high glucose concentrations

Abstract: Diabetic nephropathy is one of the most common complications of diabetes mellitus and the leading cause of end-stage renal disease. A reduction in podocyte number has been documented in the kidneys of these patients. To identify the molecular changes in podocytes that are primarily caused by high glucose (HG) concentrations and not by secondary alterations (e.g. glomerular hypertension), we investigated the protein expression profiles in a podocyte cell line under long-term HG exposure (30 versus 10 mM for 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…Podocytes utilize their dynamic cytoskeleton to maintain their complex shape and function [30] and a very recent proteomic analysis demonstrated that numerous cytoskeletal proteins are altered as a consequence of high-glucose exposure [31]. As in neuronal cells, the influence of actin dynamics on cell health is especially relevant along cell processes and our data highlight this as there was no difference in actin distribution in the cell body but a specific alteration of actin dynamics along podocyte processes was found.…”
Section: Discussionsupporting
confidence: 52%
“…Podocytes utilize their dynamic cytoskeleton to maintain their complex shape and function [30] and a very recent proteomic analysis demonstrated that numerous cytoskeletal proteins are altered as a consequence of high-glucose exposure [31]. As in neuronal cells, the influence of actin dynamics on cell health is especially relevant along cell processes and our data highlight this as there was no difference in actin distribution in the cell body but a specific alteration of actin dynamics along podocyte processes was found.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, one current study showed differential proteomic changes in an immortalized mouse podocyte cell line after long term exposure (two weeks) to HG (Schordan et al 2009). However, our study of primary cultured rat GECs exposed to HG for three days demonstrated different patterns of proteome changes compared with the above cited study.…”
Section: Discussionmentioning
confidence: 67%
“…Schordan et al observed changes in cytoskeletal proteins in cultured human podocytes under high glucose conditions and found similar changes in biopsies from patients with diabetic nephropathy 65 . Recently, we performed a proteome analysis of early and late proximal tubules prepared by hand-dissection from control animals and acidotic mice and assessed changes in protein expression by adding kidney tissue from SILAC mice (Velic, Macek, Nowik, Mann, Wagner, unpublished results).…”
Section: Application Of Proteomics To Normal and Diseased Kidney Funcmentioning
confidence: 88%
“…Substructures of glomeruli or the component of the glomerular filtration barrier, i.e. podocytes, mostly originating from the cell culture have also been investigated 65 .…”
Section: Segment-directed Proteomics In the Nephron/kidneymentioning
confidence: 99%